2017
DOI: 10.1038/emm.2017.140
|View full text |Cite|
|
Sign up to set email alerts
|

Tumor necrosis factor-inducible gene 6 protein ameliorates chronic liver damage by promoting autophagy formation in mice

Abstract: Tumor necrosis factor-inducible gene 6 protein (TSG-6) has recently been shown to protect the liver from acute damage. However, the mechanism underlying the effect of TSG-6 on the liver remains unclear. Autophagy is a catabolic process that targets cell components to lysosomes for degradation, and its functions are reported to be dysregulated in liver diseases. Here we investigate whether TSG-6 promotes liver regeneration by inducing autophagic clearance in damaged livers. Mice fed a methionine choline-deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Post-translational modification of histone proteins can markedly affect DNA accessibility to transcriptional regulators. For instance, trimethylation of different lysine residues at the N-terminus may induce either active or repressed chromatin composition [ 24 ]. To assess the importance of histone modifications in the maintenance of EC identity, we conducted Chromatin Immunoprecipitation Sequencing (ChIP-Seq) profiling of the H3K4me3 and H3K27me3 histone marks, which are enriched in active or repressed chromatin regions, respectively [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Post-translational modification of histone proteins can markedly affect DNA accessibility to transcriptional regulators. For instance, trimethylation of different lysine residues at the N-terminus may induce either active or repressed chromatin composition [ 24 ]. To assess the importance of histone modifications in the maintenance of EC identity, we conducted Chromatin Immunoprecipitation Sequencing (ChIP-Seq) profiling of the H3K4me3 and H3K27me3 histone marks, which are enriched in active or repressed chromatin regions, respectively [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The effects of TSG-6 are broad ranging (see Table 3) where these include the suppression of inflammation, the reduction of tissue injury and disease indices, and the enhancement of healing and repair processes. For instance, TSG-6 enhanced autophagy and reduced apoptosis of hepatocytes in a model of chronic liver damage [151] and had anti-fibrotic activities in acute liver injury [145], cutaneous wound healing [133] and following vein graft surgery where it limited restenosis [141]. Moreover, TSG-6 inhibited collagen expression and hypertrophic scaring in a rabbit ear model [142], but, conversely increased the production of collagens in atherosclerotic plaques of ApoE null mice [140], where it has been suggested to lead to plaque stabilization, e.g.…”
Section: The Immunomodulatory and Tissue Protective Activities Of Tsg-6mentioning
confidence: 99%
“…Recent investigations have confirmed that autophagy plays a pivotal role in the progression of chronic liver disease (Wang et al 2017 ; Liu et al 2018 ). However, few studies have focused on the relationship between autophagy and the physical function of CK19-positive HPCs.…”
Section: Discussionmentioning
confidence: 91%